Electrochemically oxidized starch composite nano silicon dioxide-based adhesive as well as preparation method and application thereof
The starch is modified through electrochemical oxidation and crosslinked with nanosilica, which solves the problem of insufficient water resistance and bonding strength of starch-based adhesives, and achieves efficient improvement of wood bonding performance and process convenience, making it suitable for industrial applications.
Patent Information
- Application Number
- CN202411468571.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-03
AI Technical Summary
The existing starch-based adhesives have insufficient water resistance and bonding strength, and the oxidant method is high in cost and long production cycle, making it difficult to control the degree of oxidation, which limits its application in the field of wood bonding.
The starch is modified by electrochemical oxidation method, and electrochemical oxidation is performed by using sodium ion salt and dilute acetic acid in the electrolytic cell, followed by adding water glass and sodium hydroxide for gelatinization, to prepare electrochemical oxidation starch composite nano-silicon dioxide Based adhesives, use chemical crosslinking to improve bond strength and water resistance, and adjust viscosity and bond strength by controlling electrochemical parameters.
It significantly improves the bonding strength and water resistance of starch-based adhesives, reduces viscosity, enhances process convenience, and has a mild process, low-price and easy-to-get raw materials, meets green and environmentally friendly requirements, and is suitable for wood bonding.
Smart Images

Figure BDA0005094089850000051 
Figure BDA0005094089850000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water-based adhesives, and in particular relates to an electrochemically oxidized starch composite nano-silicon dioxide-based adhesive and a preparation method and application thereof. Background Art
[0002] Starch is one of the most abundant renewable resources in the world. It is synthesized by plants through photosynthesis and is a completely biodegradable polysaccharide. Starch is usually a white powder with a chemical formula of [C6H 10 O5] n , which is composed of two major components, amylose and amylopectin. Starch-based adhesives have the advantages of a wide range of raw material sources, simple process, convenient operation, low cost, biodegradability, renewability, and environmental protection. However, the presence of abundant hydroxyl groups in the starch structure leads to poor water resistance of starch-based adhesives, which limits their application in the field of wood bonding (Xie Guangyang, Chen Qijie, Chen Guang, et al. Research progress of starch-based adhesives [J]. New Chemical Materials, 2022, 50(10): 31-35.).
[0003] Since starch contains a large number of hydroxyl groups, the cohesive force between hydroxyl groups and water molecules is greater than its adhesive force to the adhesive material. The viscosity of starch adhesives will be seriously reduced under humid conditions. In order to improve the water resistance of starch adhesives, the starch performance can be improved by oxidation. Under the action of oxidants, the hydroxyl groups on the glucose units of starch will be oxidized to carboxyl groups (-COOH), which significantly improves the stability of the adhesive. At the same time, oxidation can break glycosidic bonds, degrade macromolecules, reduce the molecular weight of starch, and improve flow properties. Xie Xiaoming and others used cassava starch as raw material and hydrogen peroxide as oxidant to prepare oxidized starch with good performance. (Xie Xiaoming, Xia Huaitian, He Feiyan, et al. Research on the preparation of oxidized starch adhesives with hydrogen peroxide [J]. Chemical Technology and Development, 2016, 45(3): 4-6.)
[0004] In the process of preparing oxidized starch adhesives, the oxidant oxidation method is generally used to oxidize starch. The commonly used oxidants are KMnO4, NaClO, H2O2, etc. He Ximei et al. prepared modified starch-based adhesives using H2O2 as an oxidant under alkaline conditions. The bonding strength and water resistance of the modified starch-based adhesives are significantly better than those of unmodified starch-based adhesives. (He Ximei, Li Yuanyuan, Li Yang, et al. Preparation and performance research of biomass modified starch-based wood adhesives [J]. Forestry Science and Technology Newsletter, 2020, 3: 32-35.) However, the method of using oxidants to oxidize starch is relatively expensive, the oxidized starch produced has low activity, and the production cycle is long. The oxidant method involves a complex mechanism for oxidizing starch. The degree of oxidation of the product is affected by many factors such as the amount of oxidant, time, temperature, and pH. It is not easy to control in actual industrial production. The final product is also a carboxyl group with low reactivity, which has limited improvement on the performance of starch adhesives.
[0005] Patent CN107502230B provides a method for preparing a water-based starch-based composite adhesive by an oxidation in-situ composite method, using starch as the main raw material, water glass as a nano-silicon dioxide precursor and a gelatinizing agent, and persulfate as an oxidant to prepare an oxidized starch-nano-silicon dioxide composite water-based adhesive. Due to the physical effect of nano-silicon dioxide and oxidized starch molecules, the nano-silicon dioxide serves as a cross-linking point to improve the strength and water resistance of the oxidized starch matrix after bonding and curing. However, the improvement of bonding strength and water resistance by a single physical cross-linking is still limited, and the oxidant method has limited oxidation ability for glycosidic bonds, resulting in a still high viscosity of the starch matrix. Therefore, how to further improve the bonding strength and water resistance of the adhesive, and further reduce the viscosity, and promote its practical application is of great significance. Summary of the invention
[0006] The purpose of the present invention is to provide an electrochemically oxidized starch composite nano-silica-based adhesive and a preparation method and application thereof, which significantly improves the bonding strength and water resistance of the starch-based adhesive, effectively reduces the viscosity, and enhances the process convenience during storage and sizing, and has important application value.
[0007] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0008] Provided is a method for preparing an electrochemically oxidized starch composite nano-silicon dioxide-based adhesive, comprising the following steps:
[0009] 1) preparing starch slurry, adding sodium ion salt and dilute acetic acid to carry out electrochemical oxidation, and after the electrochemical oxidation is completed, heating and adding water glass and sodium hydroxide dropwise for gelatinization to obtain an electrochemically oxidized starch composite nano-silica-based adhesive matrix;
[0010] 2) Adding a defoamer, a crosslinking agent, an emulsifier and a pigment to the adhesive matrix obtained in step 1), wherein the pigment may be added or not, to obtain an electrochemically oxidized starch composite nano-silicon dioxide-based adhesive.
[0011] According to the above scheme, in step 1), the starch is natural plant starch, specifically any one or a combination of corn starch, cassava starch, wheat starch or potato starch.
[0012] According to the above scheme, in step 1), the sodium ion salt is any one of sodium perchlorate, sodium hypochlorite, sodium periodate, sodium iodate, sodium peroxide or sodium persulfate.
[0013] According to the above scheme, in step 1), the water glass is any one of sodium water glass and potassium water glass or a combination thereof.
[0014] According to the above scheme, in step 1), the mass percentage concentration of the starch slurry is 30-40%.
[0015] According to the above scheme, in step 1), the mass of the sodium ion salt is 5-15% of the mass of the starch.
[0016] According to the above scheme, in step 1), the mass of water glass is 4-15% of the mass of starch.
[0017] According to the above scheme, in step 1), the mass of sodium hydroxide is 0.15-5% of the mass of starch.
[0018] According to the above scheme, in step 1), the concentration of dilute acetic acid is 0.1-0.3 mol / L.
[0019] According to the above scheme, in step 1), the electrochemical oxidation process is: the voltage is between 1.25-10V, the electrolysis starts at room temperature, and the current density is controlled at 0.05-2A / cm 2 , the reaction time is 1-4 hours.
[0020] According to the above scheme, in step 1), starch slurry, sodium ion salt and an appropriate amount of dilute acetic acid are added to the anode tank; and an appropriate amount of dilute acetic acid is also added to the cathode tank.
[0021] According to the above scheme, in step 1), the temperature is raised to 60-90° C. and water glass and sodium hydroxide are added dropwise for gelatinization. After the addition is completed, the mixture is kept warm and stirred for 1-2 hours.
[0022] According to the above scheme, in step 2), the emulsifier is any one or a combination of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, OP-10, and dodecyltrimethylammonium bromide.
[0023] According to the above scheme, in step 2), the defoaming agent is any one or a combination of a phosphate defoaming agent, a mineral oil defoaming agent or a silicone defoaming agent.
[0024] According to the above scheme, in step 2), the cross-linking agent is any one or a combination of borax, toluene diisocyanate, trimethylolphenol, and hexamethoxymethyl melamine.
[0025] According to the above scheme, in step 2), the pigment filler is any one or a combination of raw starch, calcium carbonate, titanium dioxide, and silicon dioxide. Whether the pigment filler is added depends on whether the system needs color.
[0026] According to the above scheme, in step 2), the mass of the defoamer is 0.1-0.5% of the mass of the starch, the mass of the emulsifier is 0.1-2.0% of the mass of the starch, the mass of the cross-linking agent is 0.1-0.6% of the mass of the starch, and the mass of the color filler is 0-30% of the mass of the starch.
[0027] Provided is an electrochemically oxidized starch composite nano-silicon dioxide-based adhesive prepared by the preparation method.
[0028] Provided is an application of the electrochemically oxidized starch composite nano-silicon dioxide-based adhesive in bonding wood.
[0029] The beneficial effects of the present invention are as follows:
[0030] 1. The present invention uses starch as the main raw material, prepares oxidized starch by electrochemical oxidation, uses water glass as a nano-silicon dioxide precursor and a gelatinizing agent, and prepares an electrochemically oxidized starch composite nano-silicon dioxide-based adhesive. Among them: electrochemical oxidation increases the degree of glycosidic bond breakage in starch and generates active groups in the starch matrix, which can induce a chemical cross-linking reaction between nano-silicon dioxide and oxidized starch, significantly improve the bonding strength and water resistance of the starch-based adhesive, and effectively reduce the viscosity, thereby enhancing its process convenience during storage and sizing, and has important application value.
[0031] 2. Furthermore, the electrochemical oxidation process of the present invention is highly controllable. By controlling the electrochemical parameters, the degree of glycosidic bond breakage in starch can be adjusted, the proportion of active groups obtained by oxidation in starch can be controlled, the degree of chemical crosslinking during the subsequent preparation of the adhesive can be controlled, and the viscosity, bonding strength and water resistance of the adhesive can be precisely controlled.
[0032] 3. The process conditions of the present invention are mild, and the main raw materials used are cheap, readily available, non-toxic and harmless. The prepared adhesive product is non-toxic and has no organic gas emissions, which meets the requirements of green environmental protection. It is used in the bonding of wood, has excellent bonding strength and corrosion resistance, and has prospects for industrial application. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] Provided is a method for preparing an electrochemically oxidized starch composite nano-silicon dioxide-based adhesive, comprising the following steps:
[0036] a. Electrochemical oxidation modification of starch: Place positive and negative graphite electrodes in an antioxidant electrolytic cell equipped with a stirring device, prepare cassava starch into a starch slurry with a mass percentage concentration of 30% in the anode cell, add 0.1 mol / L dilute acetic acid and sodium iodate; add 0.1 mol / L dilute acetic acid to the cathode cell, in which the mass of sodium ion salt sodium iodate is 5% of the mass of starch. Turn on the power, control the voltage at 1.25V, start electrolysis at room temperature, and control the current density at 0.05A / cm 2 After reacting for 1 h, the electrolysis was stopped.
[0037] b. Gelatinization modification of starch: add sodium hydroxide and sodium silicate water glass as gelatinizers to the starch slurry after electrochemical oxidation in step a, raise the temperature to 75°C, and gelatinize for 1 hour under stirring. The mass of sodium hydroxide is 0.15% of the starch, and the mass of sodium silicate water glass is 4.85% of the starch.
[0038] c. Preparation of starch adhesive: Add defoamer tributyl phosphate, crosslinker borax and emulsifier sodium dodecyl sulfate to the gelatinized starch slurry obtained in step b, and stir evenly to obtain starch adhesive. The mass of the defoamer is 0.3% of the mass of the starch, the mass of the crosslinker is 0.1% of the starch, and the mass of the emulsifier sodium dodecyl sulfate is 0.5% of the starch.
[0039] The specific properties of the starch adhesive obtained in this example are shown in Table 1.
[0040] Example 2
[0041] Provided is a method for preparing an electrochemically oxidized starch composite nano-silicon dioxide-based adhesive, comprising the following steps:
[0042] a. Electrochemical oxidation modification of starch: Place positive and negative graphite electrodes in an antioxidant electrolytic cell equipped with a stirring device, prepare cassava starch into a starch slurry with a mass percentage concentration of 35% in the anode cell, add appropriate amounts of 0.2mol / L dilute acetic acid and sodium chloride according to the capacity of the electrolytic cell; add appropriate amounts of 0.2mol / L dilute acetic acid in the cathode cell, where the mass of sodium ion salt is 10% of the mass of starch. Turn on the power, control the voltage at 5V, start electrolysis at room temperature, and control the current density at 0.5A / cm 2 After reacting for 2 h, the electrolysis was stopped.
[0043] b. Gelatinization modification of starch: sodium hydroxide and sodium silicate water glass are added as gelatinizers to the starch slurry after electrochemical oxidation in step a, and the temperature is raised to 80°C, and the gelatinization reaction is carried out for 1.5 hours under stirring, wherein the mass of sodium hydroxide is 0.3% of the starch, and the mass of sodium silicate water glass is 6.7% of the starch.
[0044] c. Preparation of starch adhesive: Add defoamer tributyl phosphate, crosslinker borax and emulsifier OP-10 to the gelatinized starch slurry obtained in step b, and stir evenly to obtain starch adhesive, wherein the mass of defoamer is 0.4% of the mass of starch, the mass of crosslinker is 0.3% of starch, and the mass of emulsifier OP-10 is 1% of starch.
[0045] The specific properties of the starch adhesive obtained in this example are shown in Table 1.
[0046] Example 3
[0047] Provided is a method for preparing an electrochemically oxidized starch composite nano-silicon dioxide-based adhesive, comprising the following steps:
[0048] a. Oxidative modification of starch: Place positive and negative graphite electrodes in an antioxidant electrolytic cell equipped with a stirring device, prepare cassava starch into a starch slurry with a mass percentage concentration of 40% in the anode cell, add appropriate amounts of 0.3 mol / L dilute acetic acid and sodium persulfate according to the capacity of the electrolytic cell; add appropriate amounts of 0.3 mol / L dilute acetic acid in the cathode cell, where the mass of sodium ion salt is 15% of the mass of starch. Turn on the power, control the voltage at 10V, start electrolysis at room temperature, and control the current density at 1A / cm 2 After reacting for 3 h, the electrolysis was stopped.
[0049] b. Gelatinization modification of starch: Add sodium hydroxide and sodium silicate water glass as gelatinizers to the starch slurry after electrochemical oxidation in step a, raise the temperature to 80°C, and gelatinize for 2 hours under stirring. The mass of sodium hydroxide is 0.5% of the starch, and the mass of sodium silicate water glass is 9.95% of the starch.
[0050] c. Preparation of starch adhesive: Add defoamer tributyl phosphate, crosslinker borax and emulsifier sodium dodecylbenzene sulfonate to the gelatinized starch slurry obtained in step b, and stir evenly to obtain starch adhesive. The mass of the defoamer is 0.5% of the mass of the starch, the mass of the crosslinker is 0.5% of the mass of the starch, and the mass of the emulsifier sodium dodecylbenzene sulfonate is 1.5% of the mass of the starch.
[0051] The specific properties of the starch adhesive obtained in this example are shown in Table 1.
[0052] Example 4
[0053] Provided is a method for preparing an electrochemically oxidized starch composite nano-silicon dioxide-based adhesive, comprising the following steps:
[0054] a. Oxidative modification of starch: Place positive and negative graphite electrodes in an antioxidant electrolytic cell equipped with a stirring device, prepare cassava starch into a starch slurry with a mass percentage concentration of 40% in the anode cell, add appropriate amounts of 0.2mol / L dilute acetic acid and sodium persulfate according to the capacity of the electrolytic cell; add appropriate amounts of 0.2mol / L dilute acetic acid in the cathode cell, where the mass of sodium ion salt is 10% of the mass of starch. Turn on the power, control the voltage at 1V, start electrolysis at room temperature, and control the current density at 0.2A / cm 2 After reacting for 2 h, the electrolysis was stopped.
[0055] b. Gelatinization modification of starch: add sodium hydroxide and sodium silicate water glass as gelatinizers to the starch slurry after electrochemical oxidation in step a, raise the temperature to 80°C, and gelatinize for 1 hour under stirring. The mass of sodium hydroxide is 5% of the starch, and the mass of sodium silicate water glass is 4% of the starch.
[0056] c. Preparation of starch adhesive: Add defoamer tributyl phosphate, crosslinker borax and emulsifier sodium dodecylbenzene sulfonate to the gelatinized starch slurry obtained in step b, and stir evenly to obtain starch adhesive. The mass of the defoamer is 0.5% of the mass of the starch, the mass of the crosslinker is 0.5% of the mass of the starch, and the mass of the emulsifier sodium dodecylbenzene sulfonate is 1.5% of the mass of the starch.
[0057] The specific properties of the starch adhesive obtained in this example are shown in Table 1.
[0058] Table 1. Performance test data of starch binders obtained in Examples 1-4
[0059]
[0060]
[0061] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an electrochemically oxidized starch composite nano-silicon dioxide-based adhesive, characterized in that: The following steps are involved: 1) preparing starch slurry, adding sodium ion salt and dilute acetic acid to carry out electrochemical oxidation, and after the electrochemical oxidation is completed, heating and adding water glass and sodium hydroxide dropwise for gelatinization to obtain an electrochemically oxidized starch composite nano-silica-based adhesive matrix; 2) adding a defoamer, a crosslinking agent, an emulsifier and a pigment filler to the adhesive matrix obtained in step 1) to obtain an electrochemically oxidized starch composite nano-silicon dioxide-based adhesive.
2. The preparation method according to claim 1, characterized in that: In the step 1), the starch is natural plant starch, specifically any one or a combination of corn starch, cassava starch, wheat starch or potato starch; the sodium ion salt is any one of sodium perchlorate, sodium hypochlorite, sodium periodate, sodium iodate, sodium peroxide or sodium persulfate.
3. The preparation method according to claim 1, characterized in that: In the step 1), the mass percentage concentration of the starch slurry is 30-40%; the concentration of the dilute acetic acid is 0.1-0.3 mol / L.
4. The preparation method according to claim 1, characterized in that: In the step 1), the mass of the sodium ion salt is 5-15% of the mass of the starch; the mass of the water glass is 5-15% of the mass of the starch; and the mass of the sodium hydroxide is 0.15-5% of the mass of the starch.
5. The preparation method according to claim 1, characterized in that: In step 1), the electrochemical oxidation process is: voltage is 1.25-10V, current density is 0.05-2A / cm 2 , the reaction time is 1-4 hours.
6. The preparation method according to claim 1, characterized in that: In the step 1), the temperature is raised to 60-90° C. and water glass and sodium hydroxide are added dropwise to gelatinize. After the addition is completed, the mixture is stirred at the temperature for 1-2 hours.
7. The preparation method according to claim 1, characterized in that: In the step 2), the emulsifier is any one or a combination of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, OP-10, and dodecyltrimethylammonium bromide; the defoamer is any one or a combination of phosphate defoamers, mineral oil defoamers, or silicone defoamers; the crosslinking agent is any one or a combination of borax, toluene diisocyanate, trimethylolphenol, and hexamethoxymethyl melamine; the color filler is any one or a combination of raw starch, calcium carbonate, titanium dioxide, and silicon dioxide.
8. The preparation method according to claim 1, characterized in that: In the step 2), the mass of the defoamer is 0.1-0.5% of the mass of the starch, the mass of the emulsifier is 0.1-2.0% of the mass of the starch, the mass of the cross-linking agent is 0.2-0.6% of the mass of the starch, and the mass of the color filler is 0-30% of the mass of the starch.
9. An electrochemically oxidized starch composite nano-silica-based adhesive prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the electrochemically oxidized starch composite nano-silicon dioxide-based adhesive according to claim 9 in bonding wood.
Citation Information
Patent Citations
A method for preparing an in-situ oxidized composite aqueous starch-based adhesive
CN107502230B